PENERAPAN GAMIFICATION PADA SISTEM INFORMASI MANAJEMEN RUANG BACA - Purma Pratama, Risqa; Oka Saputra, Komang; Care Khrisne, Duman (Jurnal SPEKTRUM, 2019)
The Reading room is a room that is used by visitors to search and study the library materials. The reading room has an important role in the learning and teaching process on campus. The Faculty of Engineering Studies of Udayana University have a reading room that is managed in a conventional way. In addition to these problems, students ' interest in visiting the Reading room is also very low. Using information technology with the Gamification method can be used to resolve the issue. This system can handle reading room management and provides convenience for users to access the reading room. The form of Gamification to be applied is the point given to the user against interactions with the Reading Room management information System. Users will be given problems that have the form and difficulty in each level, correct answers will get points and wrong answers will get a reduction of points. The points gained will be accumulated so that the level of users can be found in the leaderboard, with the mechanisms in the system expected to borrow and read books in the Reading room can increase. The Reading Room Management Information System uses 3 tests: Black Box, System usability scale, and the last of Gamification testing. Based on the test results using the black box method, the system has a function that is declared successful. Based on the test result system usability scale obtained score 70.12 expressed acceptable. In addition to the Gamification testing, a score of 3.98 is categorized by agreeing with the application